BTA BTA Examination of Sputum Samples Using the Ziehl-Neelsen Staining Method at the Pandan Hospital Laboratory, Central Tapanuli, North Sumatra : Pemeriksaan BTA pada Sampel Sputum Menggunakan Metode Pewarnaan Ziehl-Neelsen di Laboratorium RSUD Pandan, Tapanuli Tengah, Sumatera Utara - Maylizawati, Maylizawati; Handayani, Dezi (Microbiotech, 2026)
Tuberculosis (TB) remains one of the major public health problems in Indonesia. Early detection is crucial to prevent transmission and complications, especially in areas with limited laboratory facilities. This study aims to detect the presence of Mycobacterium tuberculosis in sputum samples using the Ziehl-Neelsen staining method at Pandan Regional Hospital Laboratory, Central Tapanuli, North Sumatra. The examination was conducted microscopically on stained sputum smears using carbol fuchsin, acid-alcohol, and methylene blue. The results showed acid-fast bacilli (AFB) appearing as bright red rods, with 1+ positivity observed in some samples based on IUATLD classification. Several samples were negative, possibly due to sputum quality or low bacterial load. The Ziehl-Neelsen method proved effective as an initial screening tool for TB diagnosis. Additionally, the study highlights the potential of local endophytic microorganisms as sources of antimicrobial compounds for future TB therapy. This research contributes to strengthening TB diagnostics in rural settings and encourages further exploration of biodiversity-based treatments.